Floral biology, pollination requirements and behavior of floral visitors in two species of pitaya - Muniz, João Paulo; Bomfim, Isac Gabriel; Corrêa, Márcio Cleber; Freitas, Breno (Revista Ciência Agronômica, 2019)
The present work aimed to study floral biology, pollination requirements and the behavior of floral visitors in two species of pitaya, Hylocereus undatus and H. polyrhizus, in Northeastern Brazil. The experiment was carried out through diurnal and nocturnal observations and the use of flowers bagged or accessible to visitors. Results showed that flowers of both species are similar both in anatomical and functional traits. They are large, with nocturnal anthesis onset and attract night and daytime flower visitors. The floral visitors found were sphinx moths, ants, wasps and bees, with Apis mellifera accounting for 86.1% of visits to flowers. The H. undatus species is independent of biotic pollination to set and produce large and well-shaped fruits, but H. polyrhizus shows limited self-pollination and requires biotic pollination to set fruits and also to produce larger fruits. In this case, A. mellifera appears as the most likely pollinator. It is concluded that biotic pollination deficit is a limiting factor for the productivity of H. polyrhizus, but not to H. undatus under the conditions studied and that the role of pollinators, especially A. mellifera, in the quality of the fruits produced by both pitaya species needs to be investigated.